Laterality of prefrontal hemodynamic response measured by functional near-infrared spectroscopy before and after repetitive transcranial magnetic stimulation: A potential biomarker of clinical outcome. (April 2022) - Yamazaki, Ryuichi; Inoue, Yuki; Matsuda, Yuki; Kodaka, Fumitoshi; Kitamura, Yuzuki; Kita, Yosuke; Shigeta, Masahiro; Kito, Shinsuke
Highlights: Laterality of the prefrontal hemodynamic response changed leftward after rTMS. Patients with rightward dominance at baseline had a greater reduction in MADRS score. Baseline prefrontal laterality is a possible clinical predictor of rTMS outcomes . Abstract: The factors associated with the clinical outcomes of repetitive transcranial magnetic stimulation (rTMS) in patients with major depressive disorder (MDD) remain largely unexplored. Therefore, this study aimed to examine whether rTMS can change the functional laterality of the prefrontal hemodynamic response and whether baseline functional laterality can predict the clinical outcomes of rTMS using functional near-infrared spectroscopy (fNIRS). We included 19 patients with MDD who were treated with high-frequency rTMS. The verbal fluency task was used as the activation task. We calculated the laterality index (LI) based on the task-related oxygenation response in the frontal region. First, the LI was compared before and after rTMS treatment. Second, the reduction in the Montgomery–Åsberg Depression Rating Scale (MADRS) score was compared between the rightward dominance group (pre-LI < 0) and the leftward dominance group (pre-LI ≥ 0). The findings showed a significant change in the LI after rTMS treatment. The rightward dominance group had a significantly greater reduction in MADRS score than the leftward dominance group. Subsequently, the laterality of the task-related hemodynamic response of the prefrontal region shifted leftward following left high-frequency rTMS treatment. Thus, the pre-LI calculated using fNIRS data is a possible predictor of rTMS outcomes in patients with MDD.